Exploring the Relationship between Entrepreneurial Orientation, CEO Dual Values, and SME Performance in State–Owned vs. Nonstate–Owned Enterprises in China. (November 2017) - Tang, Jintong; Tang, Zhi; Cowden, Birton J.
Most entrepreneurial orientation (EO)–performance research focuses on identifying organizational–level contingent factors in developed countries. In this study, we advance EO research by examining how CEO self–enhancing and self–transcending values shape the relationship between EO and performance, differentially, in Chinese state–owned enterprises vs. nonstate–owned enterprises. Supporting self–concern and other–orientation theory, our sample of 148 manufacturing firms in the chemical industry in Eastern China indicates that the EO–performance relationship is stronger for high self–enhancing CEOs in state–owned enterprises, whereas the focal link is stronger for low self–enhancing CEOs in nonstate–owned enterprises.